High-throughput cryopreservation of in vivo-derived swine embryos. - Lee D Spate; Clifton N Murphy; Randall S Prather (PLoS ONE, 2013)
Cryopreservation of swine embryos is inefficient. Our goal was to develop a non-invasive method for "relatively" high-throughput cryopreservation of in vivo-produced swine embryos. Since removal of the lipid droplets within early swine embryos improves cryosurvival we wanted to apply a technique of high osmolality treatment followed by centrifugation that was first developed for in vitro-produced swine embryos to in vivo-produced swine embryos. The first aim was to determine how sensitive the in vivo-produced zygote and 2-cell stage embryo was to various high osmolality conditions for a short duration. Culture for 6, 12 or 18 min at 300, 400 or 500 milliosmoles (mOsm) had no detectable affect on the resulting blastocyst stage embryos (number of inner cell mass nuclei, trophectoderm nuclei, total number of nuclei, ratio of the trophectoderm to inner cell mass nuclei or percent blastocyst). However there was an effect of gilt on each of these parameters. For the second aim we focused on 300 mOsm for 6 min, 400 mOsm for 12 min, 500 mOsm for 12 min, and 500 mOsm for 18 min. The embryos were centrifuged for the duration of high osmolality treatment, then cultured to the blastocyst stage and vitrified. After vitrification and thawing the 500 mOsm for 18 min had the highest percent re-expansion with no difference in the total number of nuclei. While requiring a different base culture medium than in vitro-produced embryos, in vivo-derived embryos also survive cryopreservation without damage to their zona pellucida.